Tobacco industry manipulation of data on and press coverage of the illicit tobacco trade in the UK. Issue Volume 23: Issue e1(2014) (10th March 2014) - Rowell, A; Evans-Reeves, K; Gilmore, A B
Abstract : Background: In the UK, transnational tobacco companies (TTCs) have been arguing that levels of illicit trade are high and increasing and will rise further if standardised packaging is implemented. This paper examines trends in and accuracy of media reporting of, and industry data on, illicit tobacco in the UK. Methods: Quantification of the volume, nature and quality of press articles citing industry data on illicit tobacco in UK newspapers from March 2008 to March 2013. Examination of published TTC data on illicit, including a comparison with independent data and of TTC reporting of Her Majesty's Revenue and Customs data on illicit. Results: Media stories citing industry data on illicit tobacco began in June 2011, 2 months after the Tobacco Control Plan for England, which heralded standardised packaging, was published. The majority of data cited are based on industry Empty Pack Surveys for which no methodology is available. For almost all parts of the country where repeat data were cited in press stories, they indicated an increase, often substantial, in non-domestic/illicit cigarettes that is not supported by independent data. Similarly, national data from two published industry sources show a sudden large increase in non-domestic product between 2011 and 2012. Yet the methodology of one report changes over this period and the other provides no published methodology. In contrast, independent data show steady declines in non-domestic and illicit cigarette penetration from 2006 to 2012 and either a continued decline or small increase to 2013. Conclusions: Industry claims that use of Non-UK Duty Paid/illicit cigarettes in the UK is sharply increasing are inconsistent with historical trends and recent independent data. TTCs are exaggerating the threat of illicit tobacco by commissioning surveys whose methodology and validity remain uncertain, planting misleading stories and misquoting government data. Industry data on levels of illicit should be treated with extreme caution.